KETOPRAK DOR SEBAGAI WARISAN BUDAYA JAWA PERANTAUAN DI SUMATERA UTARA - Suyadi nfm (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Ketoprak dor is a product of local indigenous culture of North Sumatra. This theater is derived from the existing Ketoprak art in Java. Ketoprak brought from Java is adapted and tailored to the local culture. Ketoprak dor was originally born in Simalungun, then developed in Tanah Deli as Tebingtinggi, Deliserdang, Medan, Binjai, Langkat, former East Sumatra and the peninsula. Based on this, the authors conducted a series of studies on the content and form of theater that never surfaced among Java, North Sumatra overseas. This study authors do since mid- 2009 until November 2013. Overview semiotic writers do to memermudah tracking and the description of Ketoprak dor in the province of North Sumatra Overview semiotic writers do to facilitate the tracking and the description of Ketoprak dor in the province of North Sumatra. Through this approach the authors to describe the content and form of Ketoprak dor. Therefore, this approach not only in terms of analyzing Ketoprak dor text (literature) but also contextually (the show). Of research by the author mentions, bam Ketoprak offerings is actually still survive and exist. However, the show is no longer the ancient times as often when there are weddings, circumcision and the celebration of 17's who often perceive kethoprak dor, now seen occasionally, now seen occasionally. Ketoprak dor is actually no longer belong only to Java, but it has belonged to the Malays Deli. The Javanese are easily adaptable plus the Malays who will receive large capital openness into the acculturation process.